2015
DOI: 10.1615/plasmamed.2016015722
|View full text |Cite
|
Sign up to set email alerts
|

Optical Emission Spectroscopy and Contact Angle Study of Plasma Cleaning of Titanium Alloy Surfaces: Argon Plasma

Abstract: Plasma cleaning is common in the preparation of titanium medical devices. In this study, we examine the use of continuous in situ measurements with optical emission spectroscopy (OES) during plasma cleaning and wet contact angle as a tool to assess titanium implant cleanliness. Plasma cleaning was performed in argon plasma at 66.7 Pa in a commercially available radio-frequency (RF) power plasma system using 25 or 100 W of power. During cleaning, the intensities of OES lines at 386 and 418 nm, as related to sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Plasma is as an established method for the cleaning of titanium materials to be used medically [49]. Also, plasma treatment increases surface hydrophilicity via affecting oxide layer which interacts with proteins that play role on cell attachment [28,50,51].…”
Section: Discussionmentioning
confidence: 99%
“…Plasma is as an established method for the cleaning of titanium materials to be used medically [49]. Also, plasma treatment increases surface hydrophilicity via affecting oxide layer which interacts with proteins that play role on cell attachment [28,50,51].…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] Despite these advantages, however, hydrophilization of Ti-based materials through plasma treatment is hardly used in industry because the obtained hydrophilic surface gradually converts to a hydrophobic surface with time. 15,16 Att et al reported that the hydrophilicity of Ti surfaces deteriorated when stored in air owing to the re-adsorption of contaminant hydrocarbons. 17 Therefore, to apply the plasma treatment of Ti-based materials as a surface hydrophilization process practically, the technology for modifying "non-deteriorated hydrophilic surfaces" is required.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these advantages, however, hydrophilization of Ti‐based materials through plasma treatment is hardly used in industry because the obtained hydrophilic surface gradually converts to a hydrophobic surface with time 15,16 . Att et al reported that the hydrophilicity of Ti surfaces deteriorated when stored in air owing to the re‐adsorption of contaminant hydrocarbons 17 .…”
Section: Introductionmentioning
confidence: 99%